Younger age of onset and uveitis associated with HLA-B27 and delayed diagnosis in Thai patients with axial spondyloarthritis - Naphruet Limsakul (Nature Portfolio, 2021)
Abstract To identify characteristics associated with HLA-B27, and to identify factors associated with delayed diagnosis in Thai patients with axial spondyloarthritis (axSpA). This cross-sectional study included Thai patients were diagnosed with axSpA by a rheumatologist at Siriraj Hospital. Clinical data were collected. Regression analyses were employed to identify factors associated with study outcomes. Of total 177 patients, 127 (72%) were positive HLA-B27. Uveitis [Odds ratio (OR) 4.0], age at onset of the first musculoskeletal symptom of ≤ 28 years [OR 3.5], female [OR 0.4], and psoriasis [OR 0.4] were significantly associated with HLA-B27 in multiple regression analysis. Those with positive HLA-B27 had less spinal flexibility. Elevated C-reactive protein (p = 0.012) was associated with shorter delay in diagnosis, while uveitis (p < 0.001) and younger age at onset of the first symptom (p = 0.002) were associated with longer delay in diagnosis in multiple regression analysis. Younger age at onset of the first musculoskeletal symptom and uveitis were associated with HLA-B27 and delayed diagnosis in axSpA patients. Young people with musculoskeletal symptom and uveitis should be referred to a rheumatologist to rule out or make a timely diagnosis of axSpA.